2019
DOI: 10.1038/s41598-019-52918-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth disorders in children and adolescents affected by syndromes or diseases associated with neurodysfunction

Abstract: We have observed that one in three patients admitted to the Neurological Rehabilitation Ward for Children and Adolescents due to a syndrome or disease associated with neurodysfunction is short of stature for their age. In order to identify the relationship between growth defects (short stature) and syndromes or diseases associated with neurodysfunction, we analyzed data collected during admission to the Neurological Rehabilitation Ward for Children and Adolescents. The study applied a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(50 citation statements)
references
References 21 publications
(34 reference statements)
2
46
2
Order By: Relevance
“…There is a relationship between the size of the brain and the size of the skull 30 , the body size 31 , and the neurological capacity of organisms 31 . Previous studies have shown that tetraplegia is accompanied by short stature 3 , though current studies have shown that tetraplegia is accompanied by microcephaly, which confirms the theory of encephalysis. Therefore, tetraplegia was not excluded from the analysis of relative microcephaly/macrocephaly; indeed, a proportional reduction in body size may be associated with a reduced brain size 31 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…There is a relationship between the size of the brain and the size of the skull 30 , the body size 31 , and the neurological capacity of organisms 31 . Previous studies have shown that tetraplegia is accompanied by short stature 3 , though current studies have shown that tetraplegia is accompanied by microcephaly, which confirms the theory of encephalysis. Therefore, tetraplegia was not excluded from the analysis of relative microcephaly/macrocephaly; indeed, a proportional reduction in body size may be associated with a reduced brain size 31 .…”
Section: Discussionsupporting
confidence: 74%
“…There was also one subgroup comprising patients with neuromuscular disorders (9.8%), which commonly occur without encephalopathy. Based on the expected presence and characteristics of encephalopathy 1 , 3 , the six small subgroups were combined into two larger subgroups corresponding to progressive encephalopathy (PE) (2.4%) and nonprogressive encephalopathy (NPE) (88.1%); the third group consisted of patients with neuromuscular diseases (NMDs) (9.8%). Given that neural tube defects vary greatly 17 and that surgical treatment is of key importance for development 18 , the children in this subgroup were divided based on the cause of the surgery (myelomeningocele and hydrocephalus versus myelomeningocele alone).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the patients eligible for the study were hospitalized during the period from 2012 to 2016 and presented congenital nervous system disorders or neurological syndromes with one or more neurodysfunctions visible since infancy. The following additional eligibility criteria were adopted: ages between 4–18 years (4 years of age was the beginning of the analyzed age range for three reasons: (a) because of the high percentage of children who are under 4 years of age without diagnosis [ 9 , 10 , 11 ], (b) because of the methodology adopted in the entire research project [ 2 , 13 ], (c) due to the presence of a biological frame of reference for the examined age range containing statistical characteristics of h [ 14 ], hc [ 3 ], HCI [ 13 ]), informed consent from both the children and their parents/legal guardians, availability of the measurements of h, and hc, as well as complete diagnostic data (recognition, rating on scale: Gross Motor Function Classification System—GMFCS), all of which were acquired during a single admission procedure.…”
Section: Methodsmentioning
confidence: 99%